Decoding the ACLS algorithms... Advanced Cardiac Life Support [corrected] [published erratum appears in AJN 1994 Feb;94(2)]. - Saver CL (AJN American Journal of Nursing, 1994)
These patient scenarios will clarify the logic behind the ACLS algorithms and help you work more effectively during a code.